Редукция многомерного уравнения Даламбера к двумерным уравнениям - Баранник, А.Ф.; Баранник, Л.Ф.; Фущич, В.И. (Український математичний журнал, 1994)
We give a classification of the maximal subalgebras of rank n—1 for the extended Poincare algebra AP˜(1,n), which is realized on the set of solutions of the d'Alembeit equation □u + λuk = 0. These subalgebras are used for constructing the anzatses reducing this equation to differential equations with two invariant variables.